Review Artikel: Perbandingan Efektivitas dan Efek Samping Pembrolizumab Kombinasi Kemoterapi Dengan Kemoterapi Tunggal Dalam Pengobatan Non-Small Cell Lung Cancer (NSCLC) - Dzannuba, Fadya Laila; Hilmi , Indah Laily; Sudarjat , Hadi; Shadrina , Jahra Almas; Affandhy , Adhwa’a Kaylla (Journal of Pharmaceutical and Sciences, 2025)
This review article aims to compare the effectiveness and side effects of pembrolizumab combined with chemotherapy versus chemotherapy alone in the treatment of advanced Non-Small Cell Lung Cancer (NSCLC). A systematic review was conducted using literature published between 2015 and 2024. Relevant studies were identified through databases such as Google Scholar, using keywords like "Pembrolizumab," "Side Effects," "Effectiveness," "Overall Survival (OS)," and "Progression-Free Survival (PFS)." The results showed that pembrolizumab combined with chemotherapy significantly improved Overall Survival (OS) and Progression-Free Survival (PFS) compared to chemotherapy alone. However, this combination therapy was associated with a higher frequency of side effects, such as pneumonitis and hypothyroidism. In conclusion, pembrolizumab combined with chemotherapy offers superior efficacy in prolonging survival and controlling disease progression in advanced NSCLC. However, its use requires careful patient selection and close monitoring of toxicity. These findings support pembrolizumab as a promising first-line therapy for advanced NSCLC.